1994
DOI: 10.1111/j.1365-2044.1994.tb04322.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of thiopentone and propofol with respect to the incidence of postoperative shivering

Abstract: SummaryOne hundred patients (69 female) undergoing surgical excision of three or more wisdom teeth were randomly allocated to receive either thiopentone or propofol for induction of anaesthesia. Other than the induction agent, the anaesthetic regimen was standardised for all cases. AN patients were observed for 15min after entry into the recovery area to assess the presence and intensity of shivering. Twenty-five patients in the thiopentone group (n = 50) and 11 patients in the propofol group shivered postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
8
1
1
Order By: Relevance
“…Postoperative shivering occurred in 5%–65% of patients recovering from general anesthesia and in 30% of volunteers undergoing regional anesthesia, though an extensive data search did not reveal any new study to support this observation 3. Shivering was observed to occur more frequently in the female gender and on use of thiopentone compared with propofol after general anesthesia 12. Rigor occurs commonly, as a protective response to core hypothermia, though it may occur in the presence of normothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative shivering occurred in 5%–65% of patients recovering from general anesthesia and in 30% of volunteers undergoing regional anesthesia, though an extensive data search did not reveal any new study to support this observation 3. Shivering was observed to occur more frequently in the female gender and on use of thiopentone compared with propofol after general anesthesia 12. Rigor occurs commonly, as a protective response to core hypothermia, though it may occur in the presence of normothermia.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no significant differences between the groups with regard to the type of operation and rectal temperatures were not statistically different at any time. Several other factors may have an influence on the incidence of postanesthetic shivering: volatile anesthetics, 20 thiopentone, 21 length of surgery and anesthesia, 22 uninhibited spinal reflex- Aldrete score on arrival at recovery room 8.0 (7-9) 8.5 (8-10) 8.0 (7-10) 7.5 (6-10)* 8.0 (7-10) on discharge at recovery room 24 In the present study, we found that clonidine was effective in preventing shivering compared to placebo. This is in accordance with most other studies that had shown that clonidine reduced both shivering and vasoconstriction, and that it was effective in the treatment of established shivering 1,17,25,26 and for its prophylaxis.…”
Section: R E T Rmentioning
confidence: 99%
“…Average duration in our study was approximately 110 ± 10 min more than the duration mentioned in these studies. [1418]…”
Section: Discussionmentioning
confidence: 99%